Geographic Variation in Festuca rubra L. Ploidy Levels and Systemic Fungal Endophyte Frequencies - Dirihan S; Helander M; Vare H; Gundel PE; Garibaldi LA; Irisarri JGN; Saloniemi I; Saikkonen K (PUBLIC LIBRARY SCIENCE, 2022)
Polyploidy and symbiotic Epichloe fungal endophytes are common and heritable characteristics that can facilitate environmental range expansion in grasses. Here we examined geographic patterns of polyploidy and the frequency of fungal endophyte colonized plants in 29 Festuca rubra L. populations from eight geographic sites across latitudes from Spain to northernmost Finland and Greenland. Ploidy seemed to be positively and negatively correlated with latitude and productivity, respectively. However, the correlations were nonlinear; 84% of the plants were hexaploids (2n = 6x = 42), and the positive correlation between ploidy level and latitude is the result of only four populations skewing the data. In the southern-most end of the gradient 86% of the plants were tetraploids (2n = 4x = 28), whereas in the northernmost end of the gradient one population had only octoploid plants (2n = 8x = 56). Endophytes were detected in 22 out of the 29 populations. Endophyte frequencies varied among geographic sites, and populations and habitats within geographic sites irrespective of ploidy, latitude or productivity. The highest overall endophyte frequencies were found in the southernmost end of the gradient, Spain, where 69% of plants harbored endophytes. In northern Finland, endophytes were detected in 30% of grasses but endophyte frequencies varied among populations from 0% to 75%, being higher in meadows compared to riverbanks. The endophytes were detected in 36%, 30% and 27% of the plants in Faroe Islands, Iceland and Switzerland, respectively. Practically all examined plants collected from southern Finland and Greenland were endophyte-free, whereas in other geographic sites endophyte frequencies were highly variable among populations. Common to all populations with high endophyte frequencies is heavy vertebrate grazing. We propose that the detected endophyte frequencies and ploidy levels mirror past distribution history of F. rubra after the last glaciation period, and local adaptations to past or prevailing selection forces such as vertebrate grazing.